Analyzing the Current Status of Ukrainian Seaports - Aliabieva Olga M. (Bìznes Inform, 2019)
The article is aimed at researching the current status of the port industry of Ukraine, defining the basic indicators as to the volumes of cargo processing, distribution and nomenclature. An analysis of the main sea ports of Ukraine of the Northern basin showed that the enterprises are developing unevenly. The State-owned enterprises SE «Сommercial Seaport «Yuzhnyy», SE «Khersonskyy Torhivelnyy Port», SE «Olviya» are analyzed according to the following indicators: financial, industrial, economic, investment, and innovative. Relevance of development of innovations at the mentioned enterprises is substantiated, as innovations noticeably lead to more efficient development of any enterprise. On the example of SE «Сommercial Seaport «Yuzhnyy» it is concluded that innovations do become the driving force in the efficient development of enterprise.